Pengembangan Nilai-nilai Budaya Tota'an Merpati berbasis Teori Self-Determination untuk Mengurangi Amotivasi Mahasiswa Angkatan 2021 - Sa’diyah, Halimatus; Isriyah, Mudafiatun; Masyitoh, Dewi (LPPM Institut Pendidikan Nusantara Global, 2025)
This study aims to develop a learning model based on the cultural values of Tota’an Merpati integrated with Self-Determination Theory (SDT) to reduce amotivation among 2021 cohort students. The research employed a research and development (R&D) approach using the ADDIE model and a mixed-methods design. The study involved 60 students divided into experimental and control groups. Results showed a significant decrease in amotivation scores in the experimental group (from an average of 72.3 to 55.1), while the control group remained relatively unchanged. Qualitative data supported these findings by indicating increased student autonomy, competence, and relatedness. In conclusion, integrating Tota’an Merpati cultural values with SDT effectively reduces amotivation and strengthens students’ intrinsic motivation.